Branching phenomena in nanostructure synthesis illuminated by the study of Ni-based nanocomposites. Issue 5 (12th January 2023) - Qiao, Liang; Fu, Zheng; Zhao, Wenxia; Cui, Yan; Xing, Xin; Xie, Yin; Li, Ji; Gao, Guanhui; Xuan, Zhengxi; Liu, Yang; Lee, Chaeeon; Han, Yimo; et al.
Abstract : Here we developed an ensemble of Nickel-Based nano-Composites (NBCs) to investigate the branching phenomena in solution-phase synthesis with precision and in depth. Abstract : Branching phenomena are ubiquitous in both natural and artificial crystallization processes. The branched nanostructures' emergent properties depend upon their structures, but their structural tunability is limited by an inadequate understanding of their formation mechanisms. Here we developed an ensemble of Nickel-Based nano-Composites (NBCs) to investigate branching phenomena in solution-phase synthesis with precision and in depth. NBCs of 24 morphologies, including dots, core@shell dots, hollow shells, clusters, polyhedra, platelets, dendrites, urchins, and dandelions, were synthesized through systematic adjustment of multiple synthesis parameters. Relationships between the synthesis parameters and the resultant morphologies were analyzed. Classical or non-classical models of nucleation, nascent growth, 1D growth, 2D growth, 3D reconstruction, aggregation, and carburization were defined individually and then integrated to provide a holistic view of the formation mechanism of branched NBCs. Finally, guidelines were extracted and verified to guide the rational solution-phase syntheses of branched nanomaterials with emergent biological, chemical, and physical properties for potential applications in immunology, catalysis, energy storage, and optics. Demonstrating a systematic approach for deconvoluting the formation mechanism and enhancing the synthesis tunability, this work is intended to benefit the conception, development, and improvement of analogous artificial branched nanostructures. Moreover, the progress on this front of synthesis science would, hopefully, deepen our understanding of branching phenomena in nature.